2014
DOI: 10.1088/2040-8978/16/3/035103
|View full text |Cite
|
Sign up to set email alerts
|

Negative refraction of inhomogeneous waves in lossy isotropic media

Abstract: Abstract. We theoretically study negative refraction of inhomogeneous waves at the interface of lossy isotropic media. We obtain explicit (up to the sign) expressions for the parameters of a wave transmitted through the interface between two lossy media characterized by complex permittivity and permeability. We show that the criterion of negative refraction that requires negative permittivity and permeability can be used only in the case of a homogeneous incident wave at the interface between a lossless and lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…where d 1 is the thickness of the water layer and k(ω) is equal to ω √ µ 0 ε 0 ε r (ω). In Equation (4), we used the Green function for dispersive materials as follows [27][28][29].…”
Section: Assessment Of the Impact Of Finite Rise Time And Materials DImentioning
confidence: 99%
See 1 more Smart Citation
“…where d 1 is the thickness of the water layer and k(ω) is equal to ω √ µ 0 ε 0 ε r (ω). In Equation (4), we used the Green function for dispersive materials as follows [27][28][29].…”
Section: Assessment Of the Impact Of Finite Rise Time And Materials DImentioning
confidence: 99%
“…Based on Fresnel's equation, reflection coefficient is a function of electromagnetic parameters at the sides of the interface as well as the angle of incidence. Based on the electromagnetic boundary condition as well as Snell's law, one can write (21), which is appropriate for a lossy-lossy interface while assuming that µ r = 1 for two sides of the interface [29,33,34].…”
Section: Systematic Error Due To Changes In the Permittivity By Meansmentioning
confidence: 99%
“…[8][9][10] Other generalized versions of the Snell's laws are based on complex or real valued boundary conditions, and quite different results are obtained. [11][12][13][14][15] Moreover, the experimental verification is extremely difficult because the associated heavy absorption results in opacity and a very short penetration depth. Chen's group carried out a series of experiments to measure the light refraction at a pure Ag/air or Au/air interface, and a negative refraction effect was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is difficult to study the influence of incident angle θ i on the light refraction. [7,11,15] In this work, we study the light refraction at a planar lossy interface, which can be applied to either Drude medium or anomalous dispersion medium. [18] According to the Krames-Kronig relation, the real part of the permittivity exhibits rapid variation in the neighborhood of heavy absorption, which leads to a peculiar equifrequency contour in the wave vector space.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has also been interest on the phenomenon of negative refraction, which usually requires media with negative permittivity and permeability [22,23,24]. However, Federov et al [23] showed that this negative refraction can also occur in conventional lossy materials if their interfaces are properly oriented, in particular, considering a metallic prism lying on the surface of another metal.…”
Section: Introductionmentioning
confidence: 99%